(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): The aim of this study was to evaluate the association of serum C-reactive protein (CRP) in preeclampsia (PE) and its effect on fetal birth weight. Materials and methods: This case control study was conducted in Chittagong Medical College Hospital, Bangladesh, from July 2013 to June 2014. Study population was pregnant women of third trimester with preeclampsia (case group) and normal blood pressure (control group). The maternal serum C-reactive protein (CRP) levels were measured by immune turbidometric assay between 32 weeks to term. The women were divided into three groups: mild PE, severe PE (according to ACOG criteria) and normal healthy group. The value of CRP and its correlation with birth weight was compared between groups. Results: One hundred and fifty (150) pregnant women were analyzed. Among them 50 were case and 100 control. There was no difference between age of the patients of both groups. The mean systolic blood pressure was 148.40 ± 12.35 mm Hg in case and 122.15 ± 6.44 mmHg in control group. The mean diastolic blood pressure was 100.00 ± 9.74 mmHg in case and 74.05 ± 5.97 mmHg for the control. The systolic and diastolic blood pressure was significantly higher in preeclamptic group (P < 0.000). C-reactive protein was 10.28 ± 7.25 mg/ mL in mild PE and 10.94 ± 6.32 mg/mL in severe PE and 3.45 ± 1.71 mg/mL in normotensive group, which was significantly higher in case than control group (P = 0.000). Preeclamptic women delivered at a significantly shorter gestational age than normal pregnant women. Mean gestational age during delivery for the case group and control group was 39.02 ± 1.6 and 39.58 ± 0.8 weeks respectively. Mean birth weight in PE (2.52 ± 0.42 kg) was significantly lower than normal pregnancies (2.88 ± 0.29 kg). The sensitivity and specificity of CRP were 68% and 98% respectively. Multiple regression analysis showed that there is a strong association between CRP levels and PE and birth weight. Conclusion: This small study showed that in case group CRP was raised in 68% cases which is much higher in comparison to healthy control group where CRP was high only in 2% cases. High CRP has association with low birth weight. Therefore, CRP may be used as cost effective investigation to identify the risk of preeclampsia and its effect on fetal birth weight. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 75-80